2022
DOI: 10.3390/jpm12060858
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine and Metabolic Illnesses in Young Adults with Prader–Willi Syndrome

Abstract: Prader–Willi syndrome (PWS) is a rare genetic disorder characterized by an insatiable appetite that leads to morbid obesity. Previous studies reported health problems in adults with PWS. However, studies on younger adults are lacking, and there are no specific studies of endocrine and metabolic illness in this age group. We performed a retrospective cohort study of 68 individuals with PWS aged 19 to 34 years at Samsung Medical Center. The prevalence of endocrine and metabolic illnesses were compared with those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…The prevalence of osteoporosis found in this study is in line with previous studies in adults with PWS that showed a prevalence of 2% to 26% ( 8 , 10–12 , 75 ). However, not all studies performed a systematic screening for osteoporosis using DXA scans, likely leading to an underestimation of the true prevalence in these studies.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of osteoporosis found in this study is in line with previous studies in adults with PWS that showed a prevalence of 2% to 26% ( 8 , 10–12 , 75 ). However, not all studies performed a systematic screening for osteoporosis using DXA scans, likely leading to an underestimation of the true prevalence in these studies.…”
Section: Discussionsupporting
confidence: 92%
“…Most of them were diagnosed with either Prader–Willi Syndrome or Down Syndrome. Prader–Willi syndrome is a rare genetic disorder characterized by muscular hypotonia, dysmorphic features, low lean body mass, mental retardation, behavioral abnormalities, and an insatiable appetite that leads to morbid obesity [ 65 , 66 ]. In these patients, persistently high serum levels of ghrelin (a hormone produced by gastric mucosa which normally stimulates short-term food intake during starvation) play a central role in promoting hyperphagia, increasing appetite, weight gain, and obesity, thus increasing the risk of obesity-related comorbidities such as dyslipidemia [ 67 ].…”
Section: Discussionmentioning
confidence: 99%